2021
DOI: 10.1371/journal.pone.0251876
|View full text |Cite
|
Sign up to set email alerts
|

Can we screen for pancreatic cancer? Identifying a sub-population of patients at high risk of subsequent diagnosis using machine learning techniques applied to primary care data

Abstract: Background Pancreatic cancer (PC) represents a substantial public health burden. Pancreatic cancer patients have very low survival due to the difficulty of identifying cancers early when the tumour is localised to the site of origin and treatable. Recent progress has been made in identifying biomarkers for PC in the blood and urine, but these cannot be used for population-based screening as this would be prohibitively expensive and potentially harmful. Methods We conducted a case-control study using prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The findings are evidence in support of developing PC risk-stratification strategies from routine medical records through the assessment of individuals’ demographic, comorbidity and lifestyle profile. When it comes to implementation in the clinical settings, the identified risk factors can be used as indication for primary care-based surveillance, if not serving as the first sieve in a multi-stage, targeted screening model [ 41 ], with a realistic expectation of identifying patients with “silent” non-cancerous pancreatic conditions in the process. Considering the well-documented probability of progression to PC from pancreatitis and cystic neoplasm [ 2 , 3 , 42 , 43 ], early detection of these patient groups and taking measures such as extirpation of cystic neoplasms or limitation of smoking and alcohol use [ 8 ], can be considered as a PC preventive strategy serving a broader goal.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are evidence in support of developing PC risk-stratification strategies from routine medical records through the assessment of individuals’ demographic, comorbidity and lifestyle profile. When it comes to implementation in the clinical settings, the identified risk factors can be used as indication for primary care-based surveillance, if not serving as the first sieve in a multi-stage, targeted screening model [ 41 ], with a realistic expectation of identifying patients with “silent” non-cancerous pancreatic conditions in the process. Considering the well-documented probability of progression to PC from pancreatitis and cystic neoplasm [ 2 , 3 , 42 , 43 ], early detection of these patient groups and taking measures such as extirpation of cystic neoplasms or limitation of smoking and alcohol use [ 8 ], can be considered as a PC preventive strategy serving a broader goal.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies developed 12 models for individuals with gastrointestinal (and other) symptoms, or that included alarm symptoms within the model (23,25,30,31,(33)(34)(35)(36)44,45,53), and 10 included clinical risk factors and symptoms alone (range: 0.66-0.98) (Tables 3 and 4) (23,25,(33)(34)(35)(36)44,45). One study by De Icaza et al (31) included biomarkers and symptoms in addition to clinical risk factors (C-statistic not reported) (31).…”
Section: Risk Prediction Model For Individuals With Gastrointestinal ...mentioning
confidence: 99%
“…Only a handful of research studies have used ML to build predictive models with EHR data in this field. 11 , 15 , 16 These studies have demonstrated that by leveraging AI/ML and EHRs, subpopulations at high risk for PDAC can be identified 1 to 2 years before diagnosis. Such efforts also highlight specific challenges and opportunities for improving the secondary use of EHR data with AI and innovative data science solutions.…”
Section: Electronic Health Recordsmentioning
confidence: 99%